1988
DOI: 10.2190/25xg-vve3-jw77-25cx
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analyses of Four Large-Scale Surveys of High School Drug Use 1977–1986

Abstract: The purpose of this study was to analyze the trends for almost a decade of self report drug survey data collected from high school students. Four large-scale surveys were conducted at three-year intervals beginning in 1977. The four cohort samples consisted of eleventh grade students from area high schools in Northeast Ohio. Frequency of usage, reason for taking drugs, and perceived harmfulness of fourteen categories of drugs are presented. Sex differences in drug use and perceived harmfulness are reported. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Finally, our finding that high boredom-proneness scores are related to greater somatization complaints adds empirical support to previous work that reported negative associations between boredom and eating behaviors (e.g., Martin, 1989;Pascale & Sylvester, 1988) and physical-health symptoms (e.g., Ferguson, 1973;Smith et al, 1981). It should be noted, however, that this prior work did not assess boredom levels using psychometrically sound instrumentation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Finally, our finding that high boredom-proneness scores are related to greater somatization complaints adds empirical support to previous work that reported negative associations between boredom and eating behaviors (e.g., Martin, 1989;Pascale & Sylvester, 1988) and physical-health symptoms (e.g., Ferguson, 1973;Smith et al, 1981). It should be noted, however, that this prior work did not assess boredom levels using psychometrically sound instrumentation.…”
Section: Discussionsupporting
confidence: 85%
“…Limited work, however, has been devoted to investigating the association between boredom and psychological-and physical-health symptoms. Evidence for such a relationship can be inferred from studies reporting significant, positive correlations between boredom and substance abuse and eating disorders (e.g., Abramson & Stinson, 1977;Ganley, 1989;Johnston & O'Malley, 1986;Martin, 1989;Pascale & Sylvester, 1988). Other researchers have established a connection between boredom and detrimental health effects in organizational settings.…”
mentioning
confidence: 99%
“…Certain reports concluded that when drugs were used sporadically, cognitive functions were largely unaffected [ 9 ], while others showed that people who overuse such agents did not realize how harmful they were [ 10 ]. It was also confirmed that a method for responding to trends in drug use may be established based on multiyear studies [ 11 ]. Relevant books provide information not only about trends in drug use [ 12 ], but also about groups of people with a higher tendency to use drugs (by sex, age, or plans for the future) [ 13 ].…”
Section: Introductionmentioning
confidence: 84%